Peran Gaya Kepemimpinan Transformasional Guru Terhadap Efikasi Diri Siswa dalam Berwirausaha di Sekolah Dasar - Fransisca Putri Wardhani; Jimmy Ellya Kurniawan (Universitas Negeri Surabaya, 2017)
The influence of transformational leadership style on entrepreneurial self efficacy has been widely studied within the organizational context. It is proven that transformational leadership style has an effect to entrepreneurial self efficacy. However, in the context of education, the study of the influence of transformational leadership style on students entrepreneurial self efficacy has been rarely conducted. The purpose of this study is to examine the influence of teachers transformational leadership style on entrepreneurial self efficacy among 148 elementary school students. Data were collected using the perception of teachers transformational leadership style, and students entrepreneurial self efficacy questionnaires. The subject is students of a private elementary school in Surabaya that implement entrepreneurship education. Data were analyzed using regression method. As an additional analysis, data in each dimension of transformational leadership will be partially-correlation analyzed with students entrepreneurial self efficacy. From the regression analysis, it is found that teachers transformational leadership style has a positive effect to students entrepreneurial self efficacy with the value of F = 26,298, p < 0,05. The dimension that has significant correlation with self-efficacy of student entrepreneurship is charismatic with r = 0,181, p < 0,05. While motivational inspiration, intellectual stimulation and individual considerations have no significant correlation with students entrepreneurial self efficacy.Abstrak: Kajian pengaruh gaya kepemimpinan transformasional terhadap efikasi diri dalam berwirausaha telah banyak dilaksanakan di dalam konteks organisasi dan terbukti bahwa gaya kepemimpinan transformasional memiliki pengaruh terhadap efikasi diri dalam berwirausaha. Namun dalam konteks pendidikan kewirausahaan, kajian antara gaya kepemimpinan transformasional guru dengan efikasi diri berwirausaha siswa belum banyak dilakukan. Tujuan penelitian ini adalah mengkaji pengaruh gaya kepemimpinan transformasional guru terhadap efikasi diri berwirausaha pada 148 siswa sekolah dasar. Pengumpulan data dilaksanakan dengan kuesioner persepsi terhadap gaya kepemimpinan transformasional guru dan efikasi diri berwirausaha dengan subjek penelitian siswa-siswa salah satu SD swasta di Surabaya yang menerapkan pendidikan ke wirausahaan. Data penelitian dianalisis menggunakan uji regresi. Sebagai uji tambahan, data pada setiap dimensi kepemimpinan transformasional dikorelasikan secara parsial dengan efikasi diri berwirausaha siswa. Dari uji regresi, didapatkan hasil bahwa gaya kepemimpinan transformasional guru berpengaruh positif terhadap efikasi diri berwirausaha siswa dengan nilai F = 26,298, p < 0,05. Dari keempat dimensi kepemimpinan transformasional guru, dimensi yang memiliki korelasi signifikan dengan efikasi diri berwirausaha siswa adalah kharismatik dengan r = 0,181, p < 0,05. Sedangkan dimensi inspirasi motivasional, stimulasi intelektual dan pertimbangan individual tidak memiliki korelasi signifikan dengan efikasi diri berwirausaha siswa.